Justiça climática : “cantos” de resistência da deficiência visual - Gomes, Giselly Rodrigues das Neves Silva (2019)
This thesis is part of the International Researcher’s Network for Environmental Education and Climate Justice (REAJA), which brings five countries in the dialogue network to study the climate crisis focusing on social groups facing the vulnerability. Studies by REAJA, as well as the Research Group on Environmental Education, Communication and Art (GPEA) have revealed that the climate crisis is made invisible, with little or no scientific information to protect Mato Grosso society in the event of any imminent climate disaster. These studies sharpen and emerge the motivations for conducting this research on Climate Justice and the inclusion of People with Visual Impairment, especially as many of these people are at risk when it comes to their inclusion in climate event anticipation mechanisms; and neither the government nor civil society is organized to provide shelter in the event of an imminent disaster risk situation. I start from the academic premise that one of the aims of Environmental Education is to reconnect and to feel (religare et sentire) Earth's connected webs, unnoticed in the daily chaos of the current climate situation. The objective of the research is to understand the field of climate justice and the context of vulnerabilities, risks of social and environmental disasters and resistance tactics, from an inclusive perspective for blind and shortage vision people. In this way, I was interested in their perceptions about the environment, their culture, the experience in schools, what they understand about climate risks and how they resist in the complex plot of social inclusion. These people work at the Institute of the Blind of the State of Mato Grosso - ICEMAT, the Mato Grosso Association of Blind - AMC, and the Centre for Support and Help for the Inclusion of Special Education - CASIES, in Cuiabá - Mato Grosso. The methodology employed is based on the Satian’s Imaginary Cartography, inspired by the phenomenology of the four Bachelardian elements. The results obtained, mainly by mapping the schools and homes of the visually impaired, reinforced the need for education and communication about the climate crisis. In the focus of the research, the broad formation deserves the care to delineate more inclusive perspectives in educational institutions. More broadly, the research contributes to the construction of public policies that consider the strengthening of Inclusive Education, concerning the protection systems of people with disabilities, against the disasters and risks of climate collapse.